2017
DOI: 10.1038/s41598-017-01953-4
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation for effects of urine pH on calcium oxalate crystallization, crystal-cell adhesion and internalization into renal tubular cells

Abstract: Urine pH has been thought to be an important factor that can modulate kidney stone formation. Nevertheless, there was no systematic evaluation of such pH effect. Our present study thus addressed effects of differential urine pH (4.0–8.0) on calcium oxalate (CaOx) crystallization, crystal-cell adhesion, crystal internalization into renal tubular cells, and binding of apical membrane proteins to the crystals. Microscopic examination revealed that CaOx monohydrate (COM), the pathogenic form, was crystallized with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 51 publications
1
57
0
2
Order By: Relevance
“…Calcium oxalate (CaOx) is the most common type of kidney stones, up to 75–90%, and the recurrence rate is approximately 50% within 10 years . The supersaturation, nucleation, growth, aggregation to crystals followed by direct adhesion on renal tubular epithelial cells is the general process of CaOx stones formation in the kidney, further leading to pain, urinary tract infections, chronic renal disease, and even loss of kidney function . However, the definite mechanisms regarding how and when CaOx stones damage kidney remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium oxalate (CaOx) is the most common type of kidney stones, up to 75–90%, and the recurrence rate is approximately 50% within 10 years . The supersaturation, nucleation, growth, aggregation to crystals followed by direct adhesion on renal tubular epithelial cells is the general process of CaOx stones formation in the kidney, further leading to pain, urinary tract infections, chronic renal disease, and even loss of kidney function . However, the definite mechanisms regarding how and when CaOx stones damage kidney remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The treated cells were cultured in a 6-well plate. As previously described, the cells with full confluence were incubated in DMEM containing 100 µg/ml calcium oxalate monohydrate (cOM, c0350000, Sigma) for 10 min at 37̊C in a humidified atmosphere with 5% CO 2 (23). The cells were then washed by PBS twice to remove residual cOM crystals.…”
Section: Determination Of Lactate Dehydrogenase (Ldh) the Cellsmentioning
confidence: 99%
“…Urine pH is also a very important risk factor for developing urinary stone disease. The human urine is normally slightly acidic (pH = 6.0–6.5), but it can vary between acidic (pH = 4.5) and alkaline (pH = 8.0) over a period of 24 h depending on diet, medication intake, timing or the presence of infection or disease. It has been reported that certain disorders, physiological conditions, and medication intake may increase the normal upper urine pH range to values even above pH = 8.0 .…”
Section: Introductionmentioning
confidence: 99%
“…Calcium oxalate crystallizes in three modifications: calcium oxalate monohydrate (COM, CaC 2 O 4 ·H 2 O, Whewellite), calcium oxalate dihydrate (COD, CaC 2 O 4 ·2H 2 O, Weddellite), and calcium oxalate trihydrate (COT, CaC 2 O 4 ·3H 2 O, Caoxite) . COM is the most common and thermodynamically stable (least soluble) phase and is more pathogenic for kidney stone formation because of its higher adhesive capability . COM crystallizes in the monoclinic prismatic, hexagonal, or dendrite form .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation